2017
DOI: 10.1007/jhep01(2017)090
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Field Theory of nonsingular cosmology

Abstract: In this paper, we explore the nonsingular cosmology within the framework of the Effective Field Theory (EFT) of cosmological perturbations. Due to the recently proved no-go theorem, any nonsingular cosmological models based on the cubic Galileon suffer from pathologies. We show how the EFT could help us clarify the origin of the no-go theorem, and offer us solutions to break the no-go. Particularly, we point out that the gradient instability can be removed by using some spatial derivative operators in EFT. Bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
155
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(157 citation statements)
references
References 86 publications
2
155
0
Order By: Relevance
“…Recently, it has been found in refs. [8,9] that the operator R (3) δg 00 in EFT of nonsingular cosmologies is significant for the stability of bounce. Here, based on the covariant description of the R (3) δg 00 operator, we propose a covariant theory (3.1) for stable nonsingular bounce.…”
Section: Jhep09(2017)027 4 Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, it has been found in refs. [8,9] that the operator R (3) δg 00 in EFT of nonsingular cosmologies is significant for the stability of bounce. Here, based on the covariant description of the R (3) δg 00 operator, we propose a covariant theory (3.1) for stable nonsingular bounce.…”
Section: Jhep09(2017)027 4 Discussionmentioning
confidence: 99%
“…Our (3.1) is actually a subclass of the DHOST theory [22,23], but the cosmological background is set only by P (φ, X). The P (φ, X) nonsingular bounce model could be ghostfree [31,37], but suffers the problem of c 2 s < 0, which can not be dispelled by using the Galileon interaction ∼ φ [6][7][8][9]. Actually, in [10,38], it is observed that the Galileon interaction only moves the period of c 2 s < 0 to the outside of the bounce phase, but can not remove it, see also earlier [39].…”
Section: Jhep09(2017)027 4 Discussionmentioning
confidence: 99%
See 3 more Smart Citations